Signs and Symbols: A Visual Culture Study of Civilization Markers in the Yangtze River Basin - Ouyang, Hui; Wang, Xi (Journal of Ecohumanism, 2025)
This study employs visual culture theory and semiotics theory to systematically examine the visual symbols embedded in material cultural remains from different regions and periods of the Yangtze River Basin. The research reveals that the civilization marker system in the Yangtze River Basin exhibits the following characteristics: First, the visual symbols in material cultural remains are diverse, encompassing archaeological sites, cultural relics, architectural symbols, and artifact patterns; Second, the diachronic evolution of symbols reflects a developmental trajectory from images to symbols to text, demonstrating shifts in social structure and cultural concepts; Third, symbol systems from different regions maintain their uniqueness while influencing each other, forming a unified yet diverse civilizational pattern; Fourth, these visual symbols embody ecological wisdom of harmony between humans and nature, humanistic spirit of respect for ritual and ethics, and enduring creative vitality. The study concludes that in-depth research of civilization markers in the Yangtze River Basin has significant theoretical and practical value for inheriting cultural genes, strengthening cultural confidence, and promoting the creative transformation and innovative development of Chinese culture.